Digital Transformation of Court Proceedings, Artificial Intelligence and the Principles of Civil Procedure - Harsági, Viktória (Pázmány Law Review, 2025)
The article analyses the relationship between artificial intelligence and the principles of civil procedure law. It pays attention to fields of tension, future challenges and how we should draw the limits of the introducing of AI in civil justice.